Chrysin sensitizes glioblastoma cells and spheroids to temozolomide treatment by reducing EMT and stemness phenotypes, as well as targeting multidrug resistance proteins - Aksüt, Yunus; Şengelen, Aslıhan; Gürsoy, Dudu Melek; Öğütcü, İrem; Kuvet, Özge; Pekmez, Murat (Frontiers in Pharmacology, 2025)
BackgroundGlioblastoma (GB, grade-IV astrocytoma) is a highly aggressive brain tumor often resistant to treatment with temozolomide (TMZ) due to multidrug resistance (MDR). Researchers are investigating natural compounds, such as chrysin (CHR), with anti-cancer properties; however, its ability to overcome drug resistance remains unclear. This study aimed to evaluate the possible synergistic effects of CHR and TMZ on glioblastoma cells in 2D- and 3D-culture models.MethodsBased on cytotoxicity (MTT test) and synergism analysis, U-87MG cells were treated with CHR (25 μM) and TMZ (250 μM), individually or combined, for 48 hours. Clonogenicity, migration, and invasion were assessed. Fluorescence staining was used to assess MtMP collapse, ER stress, autophagy, apoptosis, and target protein localization. Protein level alterations were measured using Western blotting, and network pharmacology was used to identify shared molecular targets. Antitumor effects were also assessed in 3D-tumor spheroids (mimics in vivo tumors), through viability and growth analyses.ResultsThe combined treatment was more effective in reducing cell proliferation than either agent alone, in a dose- and time-dependent manner. CHR increased TMZ cytotoxicity by promoting mitochondrial dysfunction, ER stress, autophagy, and apoptosis, and further decreased motility, clonogenicity, EMT status, and stem-like traits. Co-treatment also suppressed the TMZ-induced upregulation and nuclear translocation of P-glycoprotein (identified as a key CHR target through network pharmacology analysis) and NF-κB-p65, as well as reduced the expression of stress proteins (Hsp60, Hsp70, Hsp90) and MRP1. In 3D spheroid models, co-treatments significantly impaired growth and viability.ConclusionThese findings suggest that CHR may be a promising adjuvant to TMZ therapy, providing novel insights into overcoming chemoresistance in GB treatment.